Aware but confused: conflicted between individual and collective responsibility. A grounded theory study of norms and organisational structures relating to sexual harassment among university students in southern Sweden - Palmieri, Jack ; 0000-0002-7430-3157; Emmelin, Maria; Svensson, Pia; Agardh, Anette ; 0000-0002-1879-7244 (International Journal of Qualitative Studies on Health and Well-being, 2025)
Purpose Sexual harassment in contexts of higher education is a well-documented problem with far reaching consequences for individuals and organizations. Questions remain about how sexual harassment is conceptualized and what implications these conceptualizations have for designing programmes to prevent and respond to sexual harassment in university settings. This study aimed to understand how students conceptualize sexual harassment, focussing on the influence of perceived norms and organizational structures as explanatory mechanisms. Methods This grounded theory study utilized seven focus group discussions to collect data from students at Lund University, Sweden. Results The analysis yielded one core category, “Aware but confused: conflicted between individual and collective responsibility”, supported by four categories reflecting different elements of conceptualizing and responding to sexual harassment. Sub-categories captured properties and dimensions of these categories along the continuum of individual to collective responsibility. The findings reflected an awareness among students of the occurrence of sexual harassment but confusion over definitions and assignment of responsibility. This confusion could have serious consequences for willingness to report cases of sexual harassment. Conclusion Building trust in the university system requires establishing common understandings of sexual harassment, clear and accountable pathways for reporting, and transparency of outcome when reports are made.